Aluminum-based composite reinforced with fullerene soot. (November 2019) - Yunusov, F.; Bobrynina, E.; Ma, T. J.; Larionova, T.; Okrepilov, M.; Mazin, V.; Kravchenko, S.; Yakovlev, V.; Chulkin, S.; Zaripova, D
Abstract: Al-based composites with fullerene soot have been successfully prepared using powder metallurgy route. The selected parameters of the powder preparation for extrusion are discussed. The microstructure and phase composition are analyzed by optical microscopy and XRD analysis. It is shown that carbon reacts with Al with very fine carbide particles formation, resulting in micro stress of the aluminum matrix, and providing high strength of the composite. The obtained composites have excellent strength characteristic (660MPa) and satisfactory ductility (4.5%). It was shown that the developed Al-based composites can successfully compete with the best aluminum alloys used for electrical wire production.